An Integrated Model of Action Selection Distinct Modes of Cortical Control of Striatal Decision Making. [article]. - Sharpe, Melissa J.
Making decisions in environments with few choice options is easy. We select the action that results in the most valued outcome. Making decisions in more complex environments, where the same action can produce different outcomes in different conditions, is much harder. In such circumstances, we propose that accurate action selection relies on top-down control from the prelimbic and orbitofrontal cortices over striatal activity through distinct thalamostriatal circuits. We suggest that the prelimbic cortex exerts direct influence over medium spiny neurons in the dorsomedial striatum to represent the state space relevant to the current environment. Conversely, the orbitofrontal cortex is argued to track a subject's position within that state space, likely through modulation of cholinergic interneurons. -- (from the author)
Keywords: Stalnaker, Thomas; Schuck, Nicolas W; Killcross, Simon; Schoenbaum, Geoffrey; Orbitofrontal cortex; Prelimbic coretex; State; Striatum; Dorsolateral prefrontal cortex; Decision making